Soviet Russian Dialectical Materialism [Diamat]
193 p.
Keywords: This book offers a critical outline of the sources of the history, of the spirit and of the doctrines of present-day Soviet Russian Dialectical Materialism ('Diamat'), i.e. of the philosophical foundations of Marxism Leninism. It is scarcely necessary to stress the usefulness of a short outline of this kind, as Russian sources are not easily accessible in the West and as it is of considerable interest to know the doctrines which make up the faith of the Communists* in all countries. The material for this book was first made public in a series of lectures at the University of Fribourg (Switzerland), first in French in the summer term of 1949, later in English at the Summer School in the same year. The French text, slightly expanded, was translated into German by Miss M. Hoerkens, Dipl. rer. pol. Various imperfections in the wording of the text and in the bibliography can be explained by the process of formation of this book. The author hopes that such imperfections will not prove disturbing.